2017
DOI: 10.12968/ijpn.2017.23.6.280
|View full text |Cite
|
Sign up to set email alerts
|

Peer mentoring supports the learning needs of nurses providing palliative care in a rural acute care setting

Abstract: Findings suggest nurses benefit from having someone to assist in learning about new documentation. Nurses respond positively to mentorship and practical guidance when integrating a new assessment form into routine evidence-based practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…It was also recommended that hospitals consider a buddy system for new staff members, which aligns with past research showing that mentoring is received positively in rural settings (McMaster et al, 2021; Mills et al, 2006; Rabbetts, 2017). In a similar vein, greater support from clinical facilitators could be achieved through more regular contact with senior mentors and having multiple mentors per staff member, which could be implemented at a local ward level.…”
Section: Discussionmentioning
confidence: 99%
“…It was also recommended that hospitals consider a buddy system for new staff members, which aligns with past research showing that mentoring is received positively in rural settings (McMaster et al, 2021; Mills et al, 2006; Rabbetts, 2017). In a similar vein, greater support from clinical facilitators could be achieved through more regular contact with senior mentors and having multiple mentors per staff member, which could be implemented at a local ward level.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has demonstrated that the age of both mentor and protégé affects perceptions of mentoring. Peer-to-peer mentoring helps both mentors and protégés to learn communication, documentation and leadership skills [41, 42]. PhD students in particular, can benefit from peer mentoring as their colleagues can assist them and socialise them into their role as future scholars [43].…”
Section: Discussionmentioning
confidence: 99%
“…Mentoring is used in healthcare as part of professional development and support, is usually dyadic in structure, with one-to-one interactions between a professional and a more senior colleague (Rabbetts, 2017, Chatburn, 2004.…”
Section: Motivation and Rewards In Nt Practice With People Affected B...mentioning
confidence: 99%